Assessment of efficience of purification of chromic waster water with application of spondyle green clay - Франчук, Г.М.; Бовсуновський, Є.О.; Рябчевський, О.В. (Proceedings of National Aviation University (archive), 2010)
Results of conducted experiments on spondyle green clay applying as a natural ecologically safe coagulant for waste water purification from Cr ions was presented. Optimal quantity of coagulant that provides the maximum level of purification was defined.